Analysis of Interfering Substances in the Measurement of Malondialdehyde Content in Plant Leaves - Sheng Wang, Yun; Di Ding, Mao; Pang, Yunli; Gang Gu, Xun; Ping Gao, Li; Xia, Tao (Asian Journal of Chemistry, 2013)
The thiobarbituric acid reactive substances assay is an easy and quick assay for the assessment in plants of lipid peroxidation, in which malondialdehyde is derivatized. To analyze the applicability of this method, the malondialdehyde concentrations in the leaves of different plants were measured by the thiobarbituric acid method. For further separation of the interfering substances, fractional extraction and gas chromatography-mass spectrometry were used in this research. The results suggest that the lipid peroxidation is accurately measured by the thiobarbituric acid method with trichloroacetic acid as the extraction solution in most plants. However, the method was not suitable for measuring the malondialdehyde concentration in golden privet (Ligustrum × vicaryi) leaves. Negative malondialdehyde concentrations were obtained in golden privet leaves by this method.